REVIEW OF CURRENT ARTICLES IN YOUTH PUBLICATION - Latipov Adilbek Polatbaevich (International Journal of Innovations in Engineering Research and Technology, 2021)
Due to today's demand, topical articles have become the main content of the press. From this point of view, this article analyzes their role in the youth publication on the basis of the necessary information.